Key Factors Influencing Digital Transformation Success and Strategic Implications for Indonesian Higher Education: Evidence From IPB University - Nurjana, Nurjana; Sukmawati, Anggraini; Koeswanda, Harry (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2025)
This study aims to identify key factors influencing the success of digital transformation at IPB University, analyze the most influential factors, and propose an optimal strategy to improve its implementation. A quantitative approach was used by distributing questionnaires to 180 respondents consisting of lecturers and educational staff at IPB University. Data were analyzed using multiple regression with SPSS. The findings reveal that digital technology and strategy significantly influence the successful implementation of digital transformation. Digital strategy has the greatest and most significant influence on the dependent variable. This means that the better the implementation of digital strategy within an organization, the higher the level of success of digital transformation. This finding confirms that targeted strategic planning, the selection of appropriate digital initiatives, and the alignment of strategy with organizational goals are crucial factors in driving successful digital transformation. Furthermore, seven key determinants influence the success of digital transformation in higher education institutions: the use of future-ready digital technology, developed digital technology systems, and technology products with user-friendly designs and optimal functionality. Alignment of strategy with the university's vision, mission, and business plan, a clear and structured digital strategy, and strategies that support cross-departmental collaboration within the organization are key determinants of digital strategy. Strengthening digital leadership and governance was identified as the top priority strategies for strengthening internal digital transformation in higher education. This research contributes to the development of digital transformation strategies in higher education, supporting Indonesia’s 2045 vision.